Tinjauan Normatif Ekonomi Islam Terhadap Perjanjian Leasing - Syamsul Arifin AR (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to examine leasing agreements from an Islamic economic perspective based on sharia principles. The method used is qualitative with a normative juridical approach, through a literature analysis of Islamic law, fatwas from scholars, and regulations related to leasing in the Islamic economic system. The results of the study show that leasing (ijarah muntahiyah bit tamlik) is justified in Islam if it fulfills the principles of justice, transparency, and does not contain elements of usury, gharar, and dzalim. In practice, some forms of conventional leasing still contain elements that contradict sharia, such as interest and unclear contracts. Therefore, a sharia-based leasing model is needed that is more in line with sharia maqashid to create a fair and sustainable economic system.